2006
DOI: 10.1051/vetres:2006038
|View full text |Cite
|
Sign up to set email alerts
|

Shedding routes ofCoxiella burnetiiin dairy cows: implications for detection and control

Abstract: -Reliable detection of Coxiella burnetii shedders is a critical point for the control of the spread of this bacterium among animals and from animals to humans. Coxiella burnetii is shed by ruminants mainly by birth products (placenta, birth fluids), but may also be shed by vaginal mucus, milk, and faeces, urine and semen. However, the informative value of these types of samples to identify shedders under field conditions is unknown. Our aim was then to describe the responses obtained using a real-time PCR tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
125
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 31 publications
9
125
1
7
Order By: Relevance
“…shell vial culture) or live animal inoculation, immunohistochemical and PCRbased detection [1,8,17,18]. Previous reports have demonstrated that viable organisms may be variably shed in the milk of dairy cattle for extended periods of greater than one year and across multiple lactations [1,7,17], and that within a herd the proportion of cows shedding in milk may range from 15 to 62% [7,9]. Our finding that 45% of cows in this commercial herd were CbPCR positive in milk samples is consistent with these previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…shell vial culture) or live animal inoculation, immunohistochemical and PCRbased detection [1,8,17,18]. Previous reports have demonstrated that viable organisms may be variably shed in the milk of dairy cattle for extended periods of greater than one year and across multiple lactations [1,7,17], and that within a herd the proportion of cows shedding in milk may range from 15 to 62% [7,9]. Our finding that 45% of cows in this commercial herd were CbPCR positive in milk samples is consistent with these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States there are currently no approved C. burnetii are inconsistent [8,15,24]. In past studies, a major limitation may have been the reliance on serology to define C. burnetii infection status, as serology is poor indicator of active C. burnetii shedding in individual animals [1,5,6,9,18]. Classically, confirmation of active infection in cattle required isolation of the organism either by laboratory animal or cell culture inoculation [1,4,7,13,16], and currently few laboratories carry out isolation due to legal limitations, risk of human exposure, and lack of sensitivity of the technique [1,9,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This quantitative approach allows one to scale different bacterium sources, with regards to the risk of Coxiella burnetii transmission among animals and from animals to humans. Coxiella burnetii is shed mainly by birth products (birth fluids, placenta), but may also be shed by cattle via vaginal mucus [7,11], milk [1,30,35], faeces [13], urine [15] and semen [19]. However, while shedding routes of Coxiella burnetii have been identified, the characteristics of Coxiella shedding in terms of kinetic and bacterial burden are still unknown.…”
Section: Introductionmentioning
confidence: 99%